Thermal resistance of 980 nm high-power laser diodes assembled at C-mounts and F-mounts. (January 2019) - Bezotosnyi, V V; Krokhin, O N; Oleshchenko, V A; Pevtsov, V F; Popov, Yu M; Cheshev, E A
Abstract: We present the experimental results regarding the thermal resistance measurements for 100 μm stripe laser diodes emitting in 980 nm spectral range. The dependence of laser thermal resistance on pumping current was measured for series of identical laser chips with resonator length 4 mm and stripe width 95 mkm assembled directly at copper C-mounts and F-mounts without thermo-compensating submounts inside the output power range 10 W and 15 W accordingly. The appropriate method of spectral envelope peak definition was used for output power range 5-15 W in which we observed spectral peculiarities associated with appearance and competition of several peaks at the spectral envelope. We have proposed an explanation of the obtained dependency based on their correlation with the dependence of the total efficiency of the laser on the pump current.